Enhancement of dissolution rate of racecadotril by liquisolid compact technology - Bhaskar Daravath; Shalini Somalanka (Universidade de São Paulo, 2023)
Abstract The current investigation was used to improve the rate of dissolution of an anti-diarrheal drug i.e., racecadotril (RT) at low pH conditions (i.e., in the stomach) by reducing the water secretion and electrolyte in to the intestine by liquisolid tablets. Different formulations (liquisolid) were prepared using Avicel PH 102 as a carrier. Aerosil 200 as a coating material and sodium starch glycolate used as a disintegrant. Polyethylene glycol 200 was used as a non-volatile vehicle to dissolve the drug. FTIR, DSC, XRD and dissolution studies were conducted to characterise liquisolid tablets. Characterisation studies indicated that no interactions between carrier and drug. Solid state characterization had shown a reduction in crystallinity that further supports increment in solubility and dissolution. The optimised formulation showed a significant increase in dissolution i.e., 99.54±0.62% in 30 min compared to directly compressible tablets (38.47±0.26%). The % dissolution efficiency of racecadotril liquisolid tablets 76.86% compared to marketed tablet (27.56%) and conventional direct compression tablet (17.11%). Significant reduction in mean dissolution time of racecadotril from liquisolid tablets (6.84 min) compared to direct compression tablet (44.57 min), indicating faster release of drug and faster onset of action. Formulation of liquisolid tablets could enhance solubility, dissolution and bioavailability of racecadotril.